Surface toll-like receptor 9 on immune cells and its immunomodulatory effect - Kou, Mengyuan; Wang, Liying (Frontiers in Immunology, 2023)
Toll like receptor 9 (TLR9) has been considered as a crucial intracellular pattern recognition receptor in the immune system, which can directly or indirectly mediate innate and adaptive immune responses by recognizing CpG DNA in endosomes to initiate its downstream signaling. However, TLR9 can also be expressed on the membrane surface of some immune and non-immune cells, called surface TLR9 (sTLR9), which covers the TLR9 and its immunomodulatory role with a mysterious veil. In this review, we mainly focus on the sTLR9 expressed on neutrophils, B cells and erythrocytes, and its immunomodulatory roles displayed alone or in coordination with endosomal TLR9 (eTLR9), providing a theoretical reference for the application of its modulators.